Answer:
6y+66
Step-by-step explanation:
write the problem out, placing 6 on its own, and the sum of y and 11 inside a pair of parentheses after the 6.
6(y+11)
then, just use the distributive property and multiply each term inside the coefficients by six. you'll get 6y+66 as your final answer.
if your teacher says that the final answer is not supposed to have variables in it, then we'll need a bit more information.
The point (1, 20) means that the total money spent for purchasing one ticket is $20.
<h3>
Linear equation</h3>
Linear equation is in the form:
y = mx + b
where y, x are variables, m is the slope of the line and b is the y intercept.
Let y represent the total money spent for buying x number of tickets.
The point (1, 20) means that the total money spent for purchasing one ticket is $20.
Find out more on linear equation at: brainly.com/question/14323743
The rule for g(x) is: ![f(x) = (x-3)^2-3](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%28x-3%29%5E2-3)
Step-by-step explanation:
Given function is:
![f(x) = x^2](https://tex.z-dn.net/?f=f%28x%29%20%3D%20x%5E2)
When a function f(x) is shifted right or left, b units the new function is written as:
![f(x) = x](https://tex.z-dn.net/?f=f%28x%29%20%3D%20x)
Shifting right
![g(x) = f(x-b)](https://tex.z-dn.net/?f=g%28x%29%20%3D%20f%28x-b%29)
Shifting left
![g(x) = f(x+b)](https://tex.z-dn.net/?f=g%28x%29%20%3D%20f%28x%2Bb%29)
Similarly, when shifting up or down
![g(x) = f(x)+b => Up\\g(x) = f(x) - b => Down](https://tex.z-dn.net/?f=g%28x%29%20%3D%20f%28x%29%2Bb%20%3D%3E%20Up%5C%5Cg%28x%29%20%3D%20f%28x%29%20-%20b%20%3D%3E%20Down)
As our given function is shifted 3 units to the right, it will be written as:
![f(x) = (x-3)^2](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%28x-3%29%5E2)
The function is when moved down 3 units, then
![f(x) = (x-3)^2-3](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%28x-3%29%5E2-3)
Hence
The rule for g(x) is: ![f(x) = (x-3)^2-3](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%28x-3%29%5E2-3)
Keywords: Function transformation, Functions
Learn more about functions at:
#LearnwithBrainly
Answer:
Step-by-step explanation:
Volume of cylinder = base area * height
height of the cylinder = Volume of the cylinder ÷ base area
= 1205.76 ÷ 200.96
= 6 in